Perkembangan Teknologi Komunikasi dalam Menunjang Fungsi Periklanan dan Public Relation - Masykuri, Nurul Candrasari (Bina Nusantara University, 2010)
Society has been flooded by advertised communication atmosphere for every product to besocialized and introduced to the public. However, there are problems arising from the consumer whenthe product being advertised is felt only one-sided communication, because in an advertised productconsumers often encounter some problems in which they cannot consider them to be their choice. Thatis why at the present time the world of advertising does not seem to be a choice in marketing a productto consumers. Article presents the relationship among advertisement, public relation, andcommunication technology in five parts, those are age sequences from agriculture to conceptual eraand its relation to advertisement and public relation, developing advertisement network and publicrelation using new technology, difference between advertisement and public relation, andcommunication technology ethic supporting advertisement and public relation.